The magnetoelectric properties of A- or B-site-doped PbVO3 films： A first-principles study - 陈星源 陈丽娟 赵宇军 (中国物理B：英文版, 2013)
We employ first-principles calculations to study the magnetic and ferroelectric properties of PbVO3 with A （XA = Ca, Sr, Bi, Ba, and La） or B （XB = Ti, Cr, Mn, Fe, Co, Ni, and Cu） site dopants, with the aim of ascertaining a large ferroelectric polarization and a long magnetic order, or even a macro fen＇i/ferromagnetism, which is critical to their potential applications in magnetoelectronic devices. It is found that PbTXAVsO24 （XA =Ca, Sr, and Ba,） are inclined to maintain the spin glass and large ferroelectric polarization. The degenerated G- and C-antiferromagnetic （AFM） couplings in the ideal PbVO3 are broken up, accompanied by the loss of ferroelectric properties, when La or Bi is doped at the A site. In contrast, the above-mentioned 3d transition elements doped at the B site of PbVO3 could induce remnant magnetic moments and preserve the large ferroelectric polarization, except for Ni and Cu. The Fe or Cr at the B site clearly remove the degenerated G- and C-AFM coupling, but the nonmagnetic Ti cannot do so. For the Mn, Co, Ni, or Cu doped at the B sites, even the two-dimensional AFM ordering in PbVO3 is destabilized. The various doping effects are further discussed with inner strain and charge transfer.